A facile approach to synthesize an oxo-functionalized graphene/polymer composite for low-voltage operating memory devices - Wang, Zhenxing; Eigler, Siegfried; Ishii, Yoshitaka; Hu, Yichen; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; Halik, Marcus (Journal of Materials Chemistry C, 2015)
Memory devices are a key technology of our era and one of the constant challenges is the reduction of their power consumption. Herein, we demonstrate that graphene oxide with very few defects, that is, about 1 nm thin oxo-functionalized graphene derivative, can be used in memory devices operating at 3 V. A memory device stores charges in the material of the active channel. Thereby, writing and erasing information can be performed at low voltage, facilitating low power consumption. To enable operation at low voltage, a novel synthetic approach is necessary. We find that the selective non-covalent electrostatic functionalization of mainly organosulfate ions is possible with dodecylammonium. This functionalization allows the non-covalent coating of flakes with a polystyrene-derivative as nm-thin dielectric medium. The resulting polymer-wrapped composite has a height of about 5 nm. We find that the thin coating of a few nm is mandatory to make the memory device work at low voltage. Furthermore, a self-assembled monolayer of an imidazolium derivative further enhances the function of the memory device. The prepared composite materials are characterized by state-of-the-art analysis including solid state nuclear magnetic resonance spectroscopy and thermogravimetric analysis coupled with gas chromatography, mass spectroscopy or infrared spectroscopy. Reference experiments prove the importance of the controlled synthesis to enable the function of the memory device.

Chemistry with Graphene and Graphene Oxide-Challenges for Synthetic Chemists - Eigler, Siegfried; Hirsch, Andreas (Angewandte Chemie International Edition, 2014)
The chemical production of graphene as well as its controlled wet chemical modification is a challenge for synthetic chemists. Furthermore, the characterization of reaction products requires sophisticated analytical methods. In this Review we first describe the structure of graphene and graphene oxide and then outline the most important synthetic methods that are used for the production of these carbon-based nanomaterials. We summarize the state-of-the-art for their chemical functionalization by noncovalent and covalent approaches. We put special emphasis on the differentiation of the terms graphite, graphene, graphite oxide, and graphene oxide. An improved fundamental knowledge of the structure and the chemical properties of graphene and graphene oxide is an important prerequisite for the development of practical applications.

Controlled Functionalization of Graphene by Oxo-addends - Eigler, Siegfried; Hirsch, Andreas (Physical Sciences Review, 2017)

Controlled functionalization of graphene oxide with sodium azide - Eigler, Siegfried; Hu, Yichen; Ishii, Yoshitaka; Hirsch, Andreas (Nanoscale, 2013)
We present the first example of azide functionalization on the surface of graphene oxide (GO), which preserves thermally unstable groups in GO through the mild reaction with sodium azide in solids. Experimental evidence, by N solid-state NMR and other spectroscopic methods, indicates the substitution of organosulfate with azide anions as the reaction mechanism. © 2013 The Royal Society of Chemistry.

Degree of functionalisation dependence of individual Raman intensities in covalent graphene derivatives - Vecera, Philipp; Eigler, Siegfried; Kolesnik-Gray, Maria; Krstic, Vojislav; Vierck, Asmus; Maultzsch, Janina; Schafer, R; Hauke, Frank; Hirsch, Andreas (Scientific Reports, 2017)
Covalent functionalisation of graphene is a continuously progressing field of research. The optical properties of such derivatives attract particular attention. In virtually all optical responses, however, an enhancement in peak intensity with increase of sp3 carbon content, and a vanishing of the peak position shift in monolayer compared to few-layer systems, is observed. The understanding of these seemingly connected phenomena is lacking. Here we demonstrate, using Raman spectroscopy and in situ electrostatic doping techniques, that the intensity is directly modulated by an additional contribution from photoluminescent p-conjugated domains surrounded by sp3 carbon regions in graphene monolayers. The findings are further underpinned by a model which correlates the individual Raman mode intensities to the degree of functionalisation. We also show that the position shift in the spectra of solvent-based and powdered functionalised graphene derivatives originates predominantly from the presence of edge-to-edge and edge-to-basal plane interactions and is by large functionalisation independent.

Determination of the Lateral Dimension of Graphene Oxide Nanosheets Using Analytical Ultracentrifugation - Walter, Johannes; Nacken, Thomas; Damm, Cornelia; Thajudeen, Thaseem; Eigler, Siegfried; Peukert, Wolfgang (Small, 2014)
In this paper, a method to determine the lateral dimensions of 2D nanosheets directly in suspension by analytical ultracentrifugation (AUC) is shown. The basis for this study is a well-characterized and stable dispersion of graphene oxide (GO) monolayers in water. A methodology is developed to correlate the sedimentation coefficient distribution measured by AUC with the lateral size distribution of the 2D GO nanosheets obtained from atomic force microscopy (AFM). A very high accuracy can be obtained by virtue of counting several thousand sheets, thereby minimizing any coating effects or statistical uncertainties. The AFM statistics are further used to fit the lateral size distribution obtained from the AUC to determine the unknown hydrodynamic sheet thickness or density. It is found that AUC can derive nanosheet diameter distributions with a relative error of the mean sheet diameter of just 0.25% as compared to the AFM analysis for 90 mass% of the particles in the distribution. The standard deviation of the size-dependent error for the total distribution is found to be 3.25%. Based on these considerations, an expression is given to calculate the cut size of 2D nanosheets in preparative centrifugation experiments.

Driving forces for the self-assembly of graphene oxide on organic monolayers - Kirschner, Johannes; Wang, Zhenxing; Eigler, Siegfried; Steinrück, Hans-Peter; Jäger, Christof; Clark, Timothy; Hirsch, Andreas; Halik, Marcus (Nanoscale, 2014)

Effect of the structure and morphology of natural, synthetic and post-processed graphites on their dispersibility and electronic properties - Kozhemyakina, Nina; Eigler, Siegfried; Inayat, Alexandra; Schwieger, Wilhelm; Hirsch, Andreas; Dinnebier, Robert E. (Fullerenes Nanotubes and Carbon Nanostructures, 2013)
Twenty-two different graphite grades of the families natural, synthetic, intercalated, expanded, amorphous, and turbostratic graphite, as well as platelets and activated carbon, were analyzed on their dispersibility in N-methylpyrrolidone, cyclohexylpyrrolidone and water-sodium cholate solution. They were characterized for their properties (grain size, density, purity, surface area, pH in water) and morphology. Thermogravimetric analysis, Raman spectroscopy studies, and electrical conductivity measurements were also used. XRPD followed by a Rietveld refinement provided information on the amounts of the rhombohedral (3R) and hexagonal (2H) phases for the crystalline part of the material and the interlayer distances. The properties of graphites favoring better dispersibility are: small grain size and bulk density, neutral pH in water. The electrical conductivity in inversely proportional to the Raman D-band intensity and is highest for the graphites with shortest interlayer spacing. The D-, G- and 2D-bands in the Raman spectra of graphites are in an exponential relation. © 2013 Copyright Taylor and Francis Group, LLC.

Extending the environmental lifetime of unpackaged perovskite solar cells through interfacial design - Chen, Haiwei; Hou, Yi; Halbig, Christian Eberhard; Chen, Shi; Zhang, Hong; Li, Ning; Guo, Fei; Tang, Xiaofeng; Gasparini, Nicola; Levchuk, Ievgen; Kahmann, Simon; Ramírez Quiroz, César Omar; et al. (Journal of Materials Chemistry A, 2016)
Solution-processed oxo-functionalized graphene (oxo-G) is employed to substitute hydrophilic PEDOT:PSS as an anode interfacial layer for perovskite solar cells. The resulting devices exhibit a reasonably high power conversion efficiency (PCE) of 15.2% in the planar inverted architecture with oxo-G as a hole transporting material (HTM), and most importantly, deploy the full open-circuit voltage (V) of up to 1.1 V. Moreover, oxo-G effectively slows down the ingress of water vapor into the device stack resulting in significantly enhanced environmental stability of unpackaged cells under illumination with 80% of the initial PCE being reached after 500 h. Without encapsulation, ∼60% of the initial PCE is retained after ∼1000 h of light soaking under 0.5 sun and ambient conditions maintaining the temperature beneath 30 °C. Moreover, the unsealed perovskite device retains 92% of its initial PCE after about 1900 h under ambient conditions and in the dark. Our results underpin that controlling water diffusion into perovskite cells through advanced interface engineering is a crucial step towards prolonged environmental stability.
Keywords: Engineering controlled terms: Cell engineering; Conducting polymers; Open circuit voltage; Perovskite; Slow light; Solar cells Environmental stability; Functionalized graphene; High power conversion; Hole-transporting materials; Interface engineering; Interfacial design; Inverted architectures; Solution-processed Engineering main heading: Perovskite solar cells

Formation and Decomposition of CO2 Intercalated Graphene Oxide - Eigler, Siegfried; Dotzer, Christoph; Hirsch, Andreas; Enzelberger-Heim, Michael; Müller, Paul (Chemistry of Materials, 2012)
The formation, stability, and decomposition of CO intercalated graphene oxide was analyzed by FTIR, TGAMS, TGA-IR, AFM, and SEM for the first time. We found that the formation starts at 50 °C and develops up to 120 °C. The formation process can be best observed by FTIR spectroscopy, and the product is stable at ambient conditions. At higher temperatures, the decomposition of CO intercalated graphene oxide occurs due to the release of water, CO , and CO that can be monitored by TGA-MS and TGA-IR analysis. AFM and SEM images can visualize the formation of blisters in GO films that become instable at 210 °C. We further prepared graphene oxide with a low water-content and found that the formation of CO was significantly suppressed and CO became the major species responsible for the weight loss. In addition we prepared OH treated graphene oxide to elucidate the formation process of CO and found C O O by TGA-MS analysis that proves the crucial role of water during CO formation. From these experiments we propose that hydrate species are key-intermediates for the formation of CO . Hence, it seems likely that rearrangement reactions that can proceed via hydrate intermediates, known from organic chemistry, are probably responsible for the formation of carboxylic acids at the edges of graphene oxide sheets after sonication of graphite oxide. Further, our investigations prove that graphene oxide is less stable than shown by TGA measurements. This has a high impact on the electronic properties of reduced graphene oxide, especially for all those using it for electronic applications. © 2012 American Chemical Society.

Graphene oxide: A stable carbon framework for functionalization - Eigler, Siegfried; Grimm, Stefan; Hof, Ferdinand; Hirsch, Andreas (Journal of Materials Chemistry A, 2013)
The effect of NaOH and HCl on the stability of the carbon framework in graphene oxide (GO) after substitution or etherification reaction in GO is demonstrated at 10 °C and 40 °C, respectively. Our results allow the preparation of functionalized GO based architectures with an intact σ-framework of carbon atoms. © 2013 The Royal Society of Chemistry.

Graphene oxide: Efficiency of reducing agents - Eigler, Siegfried; Grimm, Stefan; Enzelberger-Heim, Michael; Müller, Paul; Hirsch, Andreas (Chemical Communications, 2013)
The efficiency of reducing agents for the reduction of graphene oxide (GO) could be probed by scanning Raman spectroscopy. A film of graphene flakes derived from GO was probed to be graphene like. We also focus on the surface quality of reduced GO (rGO). © 2013 The Royal Society of Chemistry.

Influence of an extremely negatively charged porphyrin on the reversible binding kinetics of NO to Fe(III) and the subsequent reductive nitrosylation - Jee, Joo-Eun; Eigler, Siegfried; Jux, Norbert; Zahl, Achim; van Eldik, Rudi (Inorganic Chemistry, 2007)

Investigation of pentaarylazafullerenes as acceptor systems for bulk-heterojunction organic solar cells - Wessendorf, Cordula D.; Eigler, Regina; Eigler, Siegfried; Hanisch, Jonas; Hirsch, Andreas; Ahlswede, Erik (Solar Energy Materials and Solar Cells, 2015)
Keywords: Alternative acceptor; Azafullerene; BHJ solar cell; Organic photovoltaics; Raised LUMO

Investigation of the thermal stability of the carbon framework of graphene oxide - Eigler, Siegfried; Grimm, Stefan; Hirsch, Andreas (Chemistry - A European Journal, 2014)
In this study, we use our recently prepared graphene oxide (GO) with an almost intact σ-framework of carbon atoms (ai-GO) to probe the thermal stability of the carbon framework for the first time. Ai-GO exhibits few defects because CO formation is prevented during synthesis. Ai-GO was thermally treated before chemical reduction and the resulting defect density in graphene was subsequently determined by statistical Raman microscopy. Surprisingly, the carbon framework of ai-GO is stable in thin films up to 100°C. Furthermore, we find evidence for an increase in the quality of ai-GO upon annealing at 50°C before reduction. The carbon framework of GO prepared according to the popular Hummers' method (GO-c) appears to be less stable and decomposition starts at 50°C, which is qualitatively indicated by CO-trapping experiments in μm-thin films. Information about the stability of GO is important for storing, processing, and using GO in many applications. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Kinetic and mechanistic studies on the reaction of nitric oxide with a water-soluble octa-anionic iron(III) porphyrin complex - Eigler, Siegfried; Hampel, Frank; Jux, Norbert; Wolak, Maria; Zahl, Achim; van Eldik, Rudi; et al. (Inorganic Chemistry, 2005)
The polyanionic water-soluble and non-μ-oxo-dimer-forming iron porphyrin iron(III) 5,10,15,20-tetra- tert-butyl-5,5,15,15-tetrakis[2, 2-bis(carboxylato)ethyl]-5,10,15,20-tetraphenylporphyrin, (P) Fe (1), was synthesized as an octasodium salt by applying well-established porphyrin and organic chemistry procedures to bromomethylated precursor porphyrins and characterized by standard techniques such as UV-vis and H NMR spectroscopy. A single pK value of 9.26 was determined for the deprotonation of coordinated water in (P)Fe (HO) (1-H2O) present in aqueous solution at pH <9. The porphyrin complex reversibly binds NO in aqueous solution to give the mononitrosyl adduct, (P)Fe(NO )(L), where L = HO or OH. The kinetics of the binding and release of NO was studied as a function of pH, temperature, and pressure by stopped-flow and laser flash photolysis techniques. The diaqua-ligated form of the porphyrin complex binds and releases NO according to a dissociative interchange mechanism based on the positive values of the activation parameters ΔS and ΔV for the "on" and "off" reactions. The rate constant k = 6.2 × 10 M s (24°C), determined for NO binding to the monohydroxo-ligated (P)Fe(OH) (1-OH) present in solution at pH >9, is markedly lower than the corresponding value measured for 1-HO at lower pH (k = 8.2 × 10 M s , 24°C, pH 7). The observed decrease in the reactivity is contradictory to that expected for the diaqua- and monohydroxo-ligated forms of the iron(III) complex and is accounted for in terms of a mechanistic changeover observed for 1-HO and 1-OH in their reactions with NO. The mechanistic interpretation offered is further substantiated by the results of water-exchange studies performed on the polyanionic porphyrin complex as a function of pH, temperature, and pressure. © 2005 American Chemical Society.

New basic insight into reductive functionalization sequences of single walled carbon nanotubes (SWCNTs) - Hof, Ferdinand; Bosch, Sebastian; Eigler, Siegfried; Hauke, Frank; Hirsch, Andreas (Journal of the American Chemical Society, 2013)
The reactivity of reduced single walled carbon nanotubes (SWCNTs) (carbon nanotubides), prepared under strict inert conditions in a glovebox with respect to the covalent functionalization with hexyl iodide and subsequent exposure to ambient conditions (air, moisture), was systematically investigated by Raman, absorption, fluorescence, and IR spectroscopy as well as by TG/MS measurements. We have discovered that the alkylation does not lead to a complete discharging of the tubes since follow-up reactions with moisture still take place leading to mixed functionalized carbon nanotube derivatives containing H- and OH-addends (but no carboxylates) next to the hexyl groups. This was confirmed by the exposure of carbon nanotubides to ambient conditions. The degree of hexylation determined both under strict inert (ic) and ambient (ac) conditions increases with an increasing K:C ratio of the reduced SWCNT starting material. The presence of OH-groups covalently attached to the nanotubes was also confirmed by postfunctionalization reactions with 2-thiophenecarbonyl chloride, leading to the corresponding esters. Control experiments with KO give rise to the formation of the same oxygen functionalities. These combined findings allowed for the suggestions of a plausible reaction mechanism, describing all the observed reactions on the SWCNTs side walls. The amount of subsequent side reactions after the treatment of reduced SWCNTs with electrophiles is strongly influenced by the reduction potential of the electrophile, which is responsible for the extent of reoxidation. Incomplete quenching of negative charges allows stronger oxidants/electrophile (e.g., O) to perform follow-up reactions. © 2013 American Chemical Societ

Quantitative investigation of the fragmentation process and defect density evolution of oxo-functionalized graphene due to ultrasonication and milling - Halbig, Christian Eberhard; Nacken, Thomas; Walter, Johannes; Damm, Cornelia; Eigler, Siegfried; Peukert, Wolfgang (Carbon, 2016)
In the view of technical and medical applications we examined the effect of ultrasonication and ball milling of oxo-functionalized graphene bearing an almost intact carbon lattice (oxo-G) with respect to the lateral flake size reduction and defect formation in the carbon lattice for the first time. The energy input was screened for both methods and quantitative changes in lateral flake size distribution were characterized in solution by analytical ultracentrifugation (AUC) supported by atomic force microscopy (AFM). For the first time, we applied statistical Raman spectroscopy to reliably evaluate the formation of lattice defects with processing time. Surprisingly, the density of lattice defects remains unaffected with energy inputs below a limiting threshold. Furthermore, for both processing techniques, the size reduction scales with the energy input according to a power law function, which is well known for emulsification and mechanical comminution processes. With the results of this study it is possible to precisely predetermine the lateral size of flakes of oxo-G upon sonication or milling processing, preserving the carbon lattice. Understanding this controlled formation of oxo-G flakes enables target oriented technical, medical and electronic applications with tailored properties.
EAM Import::2019-03-13

Region-Selective Self-Assembly of Functionalized Carbon Allotropes from Solution - Wang, Zhenxing; Mohammadzadeh, Saeideh; Schmaltz, Thomas; Kirschner, Johannes; Khassanov, Artöm; Eigler, Siegfried; Mundloch, Udo; Backes, Claudia; Steinrück, Hans-Peter; Magerl, Andreas; Hauke, Frank; Hirsch, Andreas; et al. (Acs Nano, 2013)
Approaches for the selective self-assembly of functionalized carbon allotropes from solution are developed and validated for 0D-fullerenes, 1D-carbon nanotubes and 2D-graphene. By choosing the right molecular interaction of self-assembled monolayers (serving the surface) with the functionalization features of carbon materials, which provide the solubility but also serve the driving force for assembly, we demonstrate a region-selective and self-terminating assembly of the materials. Active layers of the carbon allotropes can be selectively deposited in the channel region of thin-film transistor (TFT) devices by this approach. As an example for a 0D system, molecules of C functionalized octadecylphosphonic acids are used to realize self-assembled monolayer field-effect transistors (SAMFETs) based on a selective molecular exchange reaction of stearic acid in the channel region. For noncovalently functionalized single-walled carbon nanotubes (SWCNTs) and graphene oxide (GO) flakes, the electrostatic Coulomb interactions between the functional groups of the carbon allotropes and the charged head groups of a SAM dielectric layer are utilized to implement the selective deposition. © 2013 American Chemical Societ

Scalable self-assembled reduced graphene oxide transistors on flexible substrate - Wang, Zhenxing; Eigler, Siegfried (Applied Physics Letters, 2014)

Statistical raman microscopy and atomic force microscopy on heterogeneous graphene obtained after reduction of graphene oxide - Eigler, Siegfried; Hof, Ferdinand; Enzelberger-Heim, Michael; Grimm, Stefan; Müller, Paul; Hirsch, Andreas (Journal of Physical Chemistry C, 2014)
Graphene oxide can be used as a precursor to graphene, but the quality of graphene flakes is highly heterogeneous. Scanning Raman microscopy (SRM) is used to characterize films of graphene derived from flakes of graphene oxide with an almost intact carbon framework (ai-GO). The defect density of these flakes is visualized in detail by analyzing the intensity and full width at half-maximum of the most pronounced Raman peaks. In addition, we superimpose the SRM results with AFM images and correlate the spectroscopic results with the morphology. Furthermore, we use the SRM technique to display the amount of defects in a film of graphene. Thus, an area of 250 × 250 μm of graphene is probed with a step-size increment of 1 μm. We are able to visualize the position of graphene flakes, edges and the substrate. Finally, we alter parameters of measurement to analyze the quality of graphene in a fast and reliable way. The described method can be used to probe and visualize the quality of graphene films. © 2014 American Chemical Society.

Sulfur species in graphene oxide - Eigler, Siegfried; Dotzer, Christoph; Hof, Ferdinand; Bauer, Walter; Hirsch, Andreas (Chemistry - A European Journal, 2013)
The structure of graphene oxide (GO) is of crucial importance for its chemical functionalization. However, the sulfur content present in GO prepared by Hummers' method has only been addressed by a few authors so far. It has been reported that hydrolysis of sulfur species takes place and that stable sulfonic groups are present in graphite oxide. In this manuscript, in contrast to earlier reports, sulfate species are identified that are covalently bound to GO and still present after extensive aqueous work-up. Additionally, we exclude the possibility that sulfonic groups are present in GO as major species after aqueous work up. Our results are based on bulk characterization of graphene oxide by thermogravimetry and subsequent analysis of the decomposition products using mass spectroscopy and infrared spectroscopy. Up to now, the combustion temperature between 200 and 300°C remained almost unaddressed. In a temperature dependant experiment we reveal two main decomposition steps that differ in temperature and that are closely related to the sulfur species in GO. While the decomposition, between 200 and 300°C, is related to the degradation of organosulfate, the other one, between 700 and 800°C, is assigned to the pyrolysis of inorganic sulfate. Furthermore, organosulfate is to some extent responsible for the reactivity of GO. Therefore, the structural model of GO was extended by adding organosulfate in addition to epoxy and hydroxyl groups, which are predominantly covalently bound above and below the carbon skeleton. Furthermore, the identification of organosulfate groups beneath epoxy groups makes new molecular architectures feasible and can be used to explain the properties of GO in various applications. Sulfur on the surface: Organosulfate was found to be an essential part of the structure of graphene oxide (see figure), which was prepared according to Hummers' protocol. These organosulfate groups play an important role in the immobilization of adsorbed species and influence the chemical reactivity of the graphene oxide. Copyright © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Visualization of defect densities in reduced graphene oxide - Eigler, Siegfried; Dotzer, Christoph; Hirsch, Andreas (Carbon, 2012)
Efficiently reducible graphene oxide (GO) was obtained, even if a high degree of functionalization is present. Graphite with few defects was used as starting material and oxidized according to Hummer's method. An extremely high I /I ratio for rGO of 2.8 (532 nm) was observed in the Raman spectrum as a consequence of the lower defect density in GO. It was also possible to demonstrate the impact of local defects on the structure in rGO by local laser exposure experiments on single graphene oxide flakes. Raman spectroscopy can visualize the laser impact by I /I ratio measurements. © 2012 Elsevier Ltd. All rights reserved.

Wet Chemical Synthesis of Graphene - Eigler, Siegfried; Enzelberger-Heim, Michael; Grimm, Stefan; Hofmann, Philipp; Kroener, Wolfgang; Geworski, Andreas; Dotzer, Christoph; Röckert, Michael; Xiao, Jie; Papp, Christian; Lytken, Ole; Steinrück, Hans-Peter; et al. (Advanced Materials, 2013)
A suitable technology for the preparation of graphene based on versatile wet chemistry is presented for the first time. The protocol allows the wet chemical synthesis of graphene from a new form of graphene oxide that consists of an intact hexagonal extgreeks-framework of C-atoms. Thus, it can be easily reduced to graphene that is no longer dominated by defects.